Pengaruh Kredit Ketahanan Pangan Dan Energi (KKPE) Terhadap Produksi Ayam Ras Pedaging Di Sumatera Barat - Astri Aminova Putri; Dwi Rachmina; Anna Fariyanti (Jurnal Agribisnis Indonesia, 2021)
Credit is an alternative capital source to support farmers in increasing production. Credit has realized by the government to farmers, in its implementation was not always used to increase production. Research shows that credit has not been used optimally for businesses financed by credit. This study aims to analyze the utilization of Food and Energy Security Credit (KKPE) and its effect on broiler production. The study was conducted in Padang Pariaman Regency, West Sumatra Province, which is known as the broiler production center. Data were collected through structured questionnaires for 85 farmers. Data were analyzed using tabulations to perform the utilized of credit to broilers. The effect of credit on broiler production was counted by calculating the alleged production using multiple linear regression broiler production functions. The results showed that the average amount of credit received by farmers amounting to Rp. 57.116.000 was not fully utilized for broilers. The average utilization for broilers is only 94,49 percent which is used to purchase broiler chicken production inputs such as chicken seedlings (DOC), feed, vitamins, drugs, vaccines, and labor wages and invest in business equipment such as animal fodder, washing machine cages and repairing cages. This research concludes credit can increase the production of broilers by 47,52 percent.